2017
DOI: 10.1016/j.ufug.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

A review of the outcomes from contracting out urban green space maintenance: What we know, don’t know and should know

Abstract: Private delivery, i.e. contracting out, of maintenance services in urban parks and green spaces has since the 1980s been spurred by neoliberal reform promises of improved performance. This article contributes to discussions of whether contracting out park and green space maintenance services is a well-performing alternative by evaluating what is knownand not knownabout the outcomes in a narrative review of thirteen studies bridging experiences from four decades and three country contexts. It is found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…Our findings concerning the changed costs from contracting out are consistent with previous research in road and park services that found lower costs with private service provision (Blom-Hansen 2003;Lindholst 2017;Petersen and Houlberg 2016). In our study, municipal road and park managers report that the latest tender reduced costs by 4.7% on average -a result statistically significant different from a situation with no cost changes.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings concerning the changed costs from contracting out are consistent with previous research in road and park services that found lower costs with private service provision (Blom-Hansen 2003;Lindholst 2017;Petersen and Houlberg 2016). In our study, municipal road and park managers report that the latest tender reduced costs by 4.7% on average -a result statistically significant different from a situation with no cost changes.…”
Section: Discussionsupporting
confidence: 89%
“…This is similar to what Bel and Costas (2006) described as 'public reforms getting rusty' and is also in line with a recent review of international empirical contracting studies (Petersen, Hjelmar, and Vrangbaek 2017). Possible mechanisms driving the diminishing returns may be that the market price (close to true production costs) is already achieved in the first tenders or that in-house provision has become increasingly efficient due to exposure to competitive pressures (Lindholst 2017). The finding highlights an important theoretical and empirical mechanism, which we believe contributes to explaining why current empirical research tends to find smaller and more mixed outcomes than early contracting literature.…”
Section: Version Accepted For Publication In Local Government Studiessupporting
confidence: 84%
See 2 more Smart Citations
“…Alonso et al, 2017;Hodge, 2000). However, from a managerial perspective, as highlighted by Lindholst andBogetoft (2011) andO'Flynn andAlford (2008), it also becomes clear that activities associated with the transaction costs of contracting out (preparing, procuring and monitoring contracts) and the required organisational changes represent a fundamentally different way of managing public service delivery -imbued with a different set of challenges, advantages and disadvantages -compared to bureaucratic modes of service delivery based on internal organisational routines and professional expertise. The implementation of contracting out is intrinsically associated with substantial changes in the organisations wherein public managers operate, entailing change in organisational structures, governing values and cultural outlook through shifts from bureaucratic modes of service provision to market-based modes 6 Version accepted for publication in Planning and Environment C: Politics and Space (Hood, 1991;.…”
Section: Public Managers and Contracting Outcomes Revisitedmentioning
confidence: 99%